2006
DOI: 10.1021/jo060847z
|View full text |Cite
|
Sign up to set email alerts
|

ZnO as a New Catalyst for N-Formylation of Amines under Solvent-Free Conditions

Abstract: The treatment of amines with formic acid in the presence of ZnO under solvent-free conditions brings about highly and efficient N-formylation to give the corresponding formamides in excellent yields. The N-formylation reaction not only involves mild conditions, simple operation, and high yields but also high chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(103 citation statements)
references
References 30 publications
2
98
0
3
Order By: Relevance
“…116 It was demonstrated that the N-formylation of both aromatic and aliphatic amines could be performed at 70°C under solvent-free conditions using ZnO as catalyst. The formamide products were obtained in good to excellent yields in 10 reaction times of 10-720 minutes (Figure 11).…”
Section: Secondary and Tertiary Amidesmentioning
confidence: 99%
See 1 more Smart Citation
“…116 It was demonstrated that the N-formylation of both aromatic and aliphatic amines could be performed at 70°C under solvent-free conditions using ZnO as catalyst. The formamide products were obtained in good to excellent yields in 10 reaction times of 10-720 minutes (Figure 11).…”
Section: Secondary and Tertiary Amidesmentioning
confidence: 99%
“…121 It was found that the previously developed 25 ZnO-catalysed N-formylation protocol failed in the case of β-lactam substrates. 116 However, the nano-sulfated TiO 2 (0.015 mol%) displayed a high catalytic activity using equimolar amounts of the β-lactams and formic acid (Scheme 32). The authors suggested that the difference in activity could be explained in terms of larger catalyst surface area and the amount of sulfuric acid suspended on the titania.…”
mentioning
confidence: 99%
“…Formamides 9a-d were obtained from the corresponding amines 8a-d by formylation using formic acid and ZnO, respectively. 23 The title compounds 1a-d were obtained by hydrolysis of formyl group using 3 M NaOH.…”
Section: Resultsmentioning
confidence: 99%
“…The physical data (mp, IR, NMR) of known compounds were found to be identical with those reported in the literature. [11][12][13][14] Spectra data for selected products: 2b. 1 …”
Section: Methodsmentioning
confidence: 99%
“…13 Recently polyethylene glycol has been reported as a medium for formylation of aniline derivatives with formic acid. 14 However, many of these methods suffer from different drawbacks such as long reaction times, high temperature, the application of expensive and toxic formylating agents and catalysts.…”
Section: Introductionmentioning
confidence: 99%